Cayley & son the life and art of Neville Henry Cayley & Neville William Cayley - Olsen, Penny (National Libr. of Australia, 2013)
The classic field guide What Bird Is That? has been known to bird enthusiasts throughout Australia for decades, ever since it was first published in 1931